REPRESENTATION OF MARXISM IN PRICE TAG SONG BY JESSIE J. - Zahrotuhayaty, Ghafera Kamelia; Fajria Novari, Ari (Universitas Hasanuddin, 2024)
This textual analysis examines the representation of Marxism in Jessie J’s song “Price Tag.” Qualitative methodology and textual analysis within a Marxist critiques the lyrics’ engagement with capitalism. Findings show “Price Tag” conveys discernible Marxist themes of anti-consumerism, anti-capitalism, alienation, and communal values. References to money and commodification are framed negatively while collective dancing is endorsed. The ubiquitous song demonstrates Marxism of profiteering, working conditions, and the reification of social relations under capitalism. However, complex concepts are diluted into accessible slogans prioritizing human dignity over materialism. The paper concludes Marxist analytics subtly permeate mainstream consciousness through lyrical assimilations. This initial textual reading indicates popular music’s continuity as a conduit for radical political thought in digestible aesthetic forms. Overall, analysis reveals Jessie J’s mass-marketed song derives theoretical substance from Marxism to advance ethical arguments. The study finds song allows marginalized political perspectives to disseminate despite commodification of artistic works under capitalism.